Investigation over the capability of MIKE 3 flow model FM to simulate the hydrodynamics and salinity distribution of hypersaline lakes: Lake Urmia (Iran) as case study. Issue 4 (2nd October 2019) - Soudi, Mina; Ahmadi, Hojjat; Yasi, Mehdi; Sibilla, Stefano; Fenocchi, Andrea; Hamidi, Sajad Ahmad
ABSTRACT: Lake Urmia, located in northwestern Iran, a hypersaline lake, divided into north and south basins by a causeway. The lake has been facing a serious environmental crisis, due to water mismanagement in the basin. To address this problem, an analysis of the hydrodynamic behavior and of salinity distribution is important. The three-dimensional numerical model MIKE 3 Flow Model FM was employed in this study. Model sensitivity analyses revealed that wind speed, friction coefficient, and vertical eddy viscosity are effective parameters on both flow velocities and salinity distribution, while bottom roughness height has minor effects on surface velocities. Reduced value for vertical eddy viscosity improves the simulation of the velocity field and has an adverse effect on salinity distribution. The UNESCO density function leads to an overestimation of density. Yet, final model results are accurate enough to reproduce the salinity distribution over the lake, revealing that the salinity difference between North and South basins of Lake Urmia increases significantly in the wet season, due to southern rivers inflows by snowmelt. For the simulated periods of 1986–1987 and 2004–2005, natural and man-induced drought hydrological conditions, the direction of flows was from south to north, with a much lower net flow in the latter period. This decrease in the exchanged flows causes higher salinity difference among basins. Results indicate that the present model could be run for any time period in both normal and drought conditions and can satisfactorily simulate the hydrodynamic characteristics and salinity distribution of Lake Urmia for management purposes.